Flame behavior and mechanical properties of polyester fabrics coated with intumescent coatings via layer-by-layer assembly. Issue 21 (November 2019) - Wattanatanom, Warunee; Charuchinda, Sireerat; Potiyaraj, Pranut
Intumescent coatings consisting of branched-polyethyleneimine (BPEI) and ammonium polyphosphate (APP) solution were successfully applied on polyester fabrics by the layer-by-layer assembly technique to enhance the flame retardant and anti-dripping properties of polyester fabrics. The surface morphology of fabrics revealed that the coatings thoroughly covered the fabrics. The assessment of the vertical burning test of thin material (UL-94 rating VTM 0) indicated that the flame retardancy of coated polyester fabrics was improved significantly as compared with the uncoated fabric. The self-extinguishing ability and anti-dripping behaviors of coated polyester fabrics were also enhanced markedly. The improvement of flame retardancy depends on the number of coating layers and the amount of APP. However, after washing, the flame retardancy decreases to some extent. The morphology of char exhibits the typical structure of intumescent char on coated fabrics. The assessment of mechanical properties revealed that the intumescent coating via layer-by-layer assembly did not deteriorate the strength of the fabric. The increasing number of coated layers leads to the slight increase of the breaking force of the fabric; however, the increasing number of layers and the increasing amount of prepared APP lead to increased rigidity of the fabrics.